2011
DOI: 10.1371/journal.pone.0014685
|View full text |Cite
|
Sign up to set email alerts
|

Milk Intake and Total Dairy Consumption: Associations with Early Menarche in NHANES 1999-2004

Abstract: BackgroundSeveral components of dairy products have been linked to earlier menarche.Methods/FindingsThis study assessed whether positive associations exist between childhood milk consumption and age at menarche or the likelihood of early menarche (<12 yrs) in a U.S sample. Data derive from the National Health and Nutrition Examination Survey (NHANES) 1999–2004. Two samples were utilized: 2657 women age 20–49 yrs and 1008 girls age 9–12 yrs. In regression analysis, a weak negative relationship was found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 82 publications
(117 reference statements)
6
81
2
5
Order By: Relevance
“…Confounding by other nutrients present in food sources of vitamin D, such as fortified milk, also seems improbable. Higher intakes of milk (23) and calcium (23,24) have each been related to earlier menarche; hence, these intakes could not explain an association of low vitamin D status with early menarche.…”
Section: Discussionmentioning
confidence: 96%
“…Confounding by other nutrients present in food sources of vitamin D, such as fortified milk, also seems improbable. Higher intakes of milk (23) and calcium (23,24) have each been related to earlier menarche; hence, these intakes could not explain an association of low vitamin D status with early menarche.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in a prospective study of 134 Iranian girls, those with milk intake at ≥34 g per day at 9 years of age had higher odds of early menarche at or before age 12 years than did girls with milk intake at <34 g per day (78). Using data from the National Health and Nutrition Examination Survey, Wiley et al (93) found that higher milk consumption at ages 5-12 years among 2,057 girls from the United States was associated with an earlier age at menarche. In other studies, dairy intake has not been related to the onset of puberty (15).…”
Section: Childhood Protein Intakementioning
confidence: 99%
“…Differences in the dietary assessment methods used may be another explanation. Assessment of intake with a single-day measure (e.g., 24-h recall) (53,78,93) may induce attenuation of the associations. Adjustment for body composition (7,61), a potential intermediate variable, could also impact the results.…”
Section: Childhood Protein Intakementioning
confidence: 99%
“…Data published by Swan et al in 2007 already suggested that maternal beef consumption may alter males' testicular development in utero and adversely affect his adult reproductive capacity (Swan et al, 2007). Even milk consumption, the hormone content of which is well known, has been associated with an increased risk of early menarche (Wiley, 2011). There are studies that find a relationship between milk and dairy products with human illnesses, such as teenagers' acne, prostate, breast, ovarian and corpus uteri cancers, many chronic diseases that are common in Western societies, as well as male reproductive disorders (Adebamowo et al, 2008;Ganmaa et al, 2011;Ganmaa et al, 2001;Givens et al, 2008;Melnik, 2009;Wiley, 2011).…”
Section: Human Health and Hormonesmentioning
confidence: 99%
“…Even milk consumption, the hormone content of which is well known, has been associated with an increased risk of early menarche (Wiley, 2011). There are studies that find a relationship between milk and dairy products with human illnesses, such as teenagers' acne, prostate, breast, ovarian and corpus uteri cancers, many chronic diseases that are common in Western societies, as well as male reproductive disorders (Adebamowo et al, 2008;Ganmaa et al, 2011;Ganmaa et al, 2001;Givens et al, 2008;Melnik, 2009;Wiley, 2011). There are many possible contributory factors to these health problems, including steroid hormones which are well known as endocrine disruption agents.…”
Section: Human Health and Hormonesmentioning
confidence: 99%